REAKSI PASAR MODAL INDONESIA SEPUTAR PEMILIHAN UMUM 8 JULI 2009 PADA SAHAM LQ-45 - Suryo Luhur (Jurnal Keuangan dan Perbankan, 2017)
This research used event study methodology to investigate the stock price reac-tion to domestic political events, Indonesian presidential and vice election on July 8th, 2009on stock of LQ-45 category listed in BEI. Data analysis used one sample t-test and pairedsamples t-test. The result of the analysis revealed that abnormal returns were: (1) not signifi-cantly different before and after presidential election announcement, (2) Significantly nega-tive on day t-10, t-5, t-4, t0, and t+7 and significantly positive on t-10 and t+7 3, (3) NotSignificantly different on day 0 Trading Volume Activity before and after presidential elec-tion announcement. This results reported here indicated that Indonesian Capital Market waslittle sensitive to political events.